The impact of meteorological forcings on gas phase air pollutants over Europe. (October 2015) - Watson, Laura; Lacressonnière, Gwendoline; Gauss, Michael; Engardt, Magnuz; Andersson, Camilla; Josse, Béatrice; Marécal, Virginie; Nyiri, Agnes; Sobolowski, Stefan; Siour, Guillaume; Vautard, Robert
Abstract: The impact of meteorological forcings on gas phase air pollutants (ozone and nitrogen dioxide) over Europe was studied using four offline chemistry transport models (CTMs) as part of the IMPACT2C project. This study uses long (20- and 30-year) simulations to evaluate the present-day performance of the CTMs, which is a necessary first step before undertaking any analysis of future air quality impacts. Two sets of meteorological forcings were used for each model: reanalysis of past observation data (ERA-Interim) and Global Climate Model (GCM) output. The results for the simulations forced by reanalysis data were assessed in relation to AirBase v7 measurement data, and it was determined that all four models slightly overpredict annual O3 values (mean biases range between 0.7 and 6.6 ppb) and three out of the four models underpredict observed annual NO2 (mean biases range between −3.1 and −5.2 ppb). The simulations forced by climate models result in spatially averaged monthly concentrations of O3 that are generally between 0 and 5 ppb higher than the values obtained from simulations forced by reanalysis data; therefore it was concluded that the use of climate models introduces an additional bias to the results, but this bias tends not to be significant in the majority of cases. The bias in O3 results appears to be correlated mainly to differences in temperature and boundary layer height between the two types of simulations, whereas the less significant bias in NO2 is negatively correlated to temperature and boundary layer height. It is also clear that the selection of chemical boundary conditions is an important factor in determining the variability of O3 model results. These results will be used as a baseline for the interpretation of future work, which will include an analysis of future climate scenarios upon European air quality. Highlights: The impacts of meteorological forcings upon chemistry transport models were studied. Long simulations (of 20 and 30 years) were performed with a set of four models. Simulations forced by reanalysis data compare well with measurements of O3 and NO2 . Climate model forcings introduce a minimal bias to the results in most cases. The bias in O3 is correlated to differences in temperature and boundary layer height.